(untitled) (Modern American Journal of Medical and Health Sciences, 2026)
Primary dysmenorrhea is a common gynecological condition characterized by painful menstrual cramps in the absence of identifiable pelvic pathology. Traditionally, the pathophysiology of primary dysmenorrhea has been attributed to excessive prostaglandin production, leading to uterine hypercontractility, reduced uterine blood flow, and ischemic pain. However, recent evidence suggests that central nervous system mechanisms may also play an important role in the development and perception of menstrual pain.